Islamic Education Methods for Junior High School Students with Special Needs - Fitri Nuraini; Tanenji Tanenji (Jurnal al-Thullab, 2022)
This study aimed to determine the method of Islamic education given to Islamic Religious Education (PAI) learning, supporting and inhibiting factors in the PAI learning process for mentally retarded children at the junior high school level at SLB ABC YPLAB Lembang. This study used a qualitative approach using descriptive analysis methods. The data collection used in this study were interviews, observation, and documentation. Based on the results of the study, it was found that the methods of Islamic education carried out in learning varied greatly such as expository methods, practical methods, recitation methods, and habituation methods which of course were also assisted by several media that supported the learning materials. The dominant Islamic education method of learning was in the form of repetition and habituation because of the condition of mentally retarded children who need special treatment. Several supporting factors, namely competent teachers and supportive parents. In addition, there were also inhibiting factors or obstacles experienced, such as minimal funds, the nature of mentally retarded children who easily forgeted and the condition of less stable children. Penelitian ini bertujuan untuk mengetahui metode pendidikan Islam yang diberikan pada pembelajaran Pendidikan Agama Islam (PAI) dan faktor pendukung dan penghambat dalam proses pembelajaran PAI bagi anak tunagrahita tingkat SMP di SLB ABC YPLAB Lembang. Penelitian ini menggunakan pendekatan jenis kualitatif dengan menggunakan metode analisis deskriptif. Pengumpulan data yang digunakan dalam penelitian ini adalah wawancara, observasi, dan dokumentasi. Berdasarkan hasil penelitian, ditemukan bahwa metode pendidikan Islam yang dilakukan pada pembelajaran sangat bervariasi seperti metode ekspositori, metode praktek, metode resitasi, dan metode pembiasaan yang tentunya dibantu juga dengan beberapa media yang menunjang materi pembelajaran tersebut. Metode pendidikan Islam yang dominan pada pembelajaran berupa pengulangan dan pembiasaan karena kondisi anak tuna grahita yang perlu ada perlakuan khusus. Beberapa faktor pendukung, yakni guru yang kompeten dan orangtua yang suportif. Selain itu ada juga faktor penghambat atau kendala yang dialami, seperti dana yang minim, sifat anak tunagrahita yang mudah lupa, dan kondisi anak yang kurang stabil.